2022
DOI: 10.1136/jitc-2022-005660
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of colorectal cancer organoids with zoledronic acid conjugated to the anti-EGFR antibody cetuximab

Abstract: BackgroundAntibody-drug conjugates (ADC) are essential therapeutic options to treat solid and hematological cancers. The anti-epidermal growth factor-receptor (EGFR) antibody cetuximab (Cet) is used for the therapy of colorectal carcinoma (CRC). Anti-CRC Vδ2 cytolytic T lymphocytes can be elicited by the priming of tumor cells with the aminobisphosphonate zoledronic acid (ZA) and consequent presentation of isopentenyl pyrophosphates through butyrophilin (BTN) family members such as BTN3A1 and BTN2A1. A major d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…Studies reported that EGFR is overexpressed in cancer cells such as colorectal, breast, and non–small cell lung cancers [ 69 , 70 , 71 ]. Due to its overexpression on cancer cells, several investigations used the third loop (L3) of transforming growth factor-α (TGF-α) to conjugate with protein antibodies [ 72 , 73 , 74 , 75 ], or full superantigen SEB to exert the toxic effect of a drug in the vicinity of cancers to achieve targeted cancer therapy [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that EGFR is overexpressed in cancer cells such as colorectal, breast, and non–small cell lung cancers [ 69 , 70 , 71 ]. Due to its overexpression on cancer cells, several investigations used the third loop (L3) of transforming growth factor-α (TGF-α) to conjugate with protein antibodies [ 72 , 73 , 74 , 75 ], or full superantigen SEB to exert the toxic effect of a drug in the vicinity of cancers to achieve targeted cancer therapy [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…IBA, RIS, and ZA were purchased from Selleckchem (Houston, TX, USA), and Cet was obtained as a leftover of the therapeutic preparation used for patients suffering from CRC (the kind gift from the Pharmacy Unit of IRCCS Ospedale Policlinico San Martino, Genoa, Italy). Cet-IBA, Cet-RIS, and Cet-ZA ADCs were prepared by Nanovex Biotechnologies (Asturias, Spain), according to the procedure reported before for the Cet-ZA (Figure 1) [30]. The protein sample was purified via ultrafiltration (100 kDa cut off) to eliminate the presence of excipients.…”
Section: Cet-iba or Cet-ris Or Cet-za Adc Synthesismentioning
confidence: 99%
“…Then, these incubation cells were lysed and subjected to Western blot (WB) analysis. WB was performed as described in detail [30]. Briefly, 30 µg/lane of total protein from 4 × 10 6 CRC cell lines Caco-2 or HCT-116 extracted with RIPA buffer were run on 8% PAGE gels (Express Plus, GenScript, Piscataway, NJ, USA) and blotted on PVDF membranes (GE-healthcare, Milan, Italy).…”
Section: Western Blot On Crc Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations